Implementasi Model Pembelajaran Inovatif: Konstruktivistik dan Kooperatif Dalam Meningkatkan Kreativitas Anak Usia Dini - Ratu Pranatalia; Rifka Siva Sinaga; Marisa Aulia Gea (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Researchers discuss the Implementation of Innovative Learning Models: Constructivist and Cooperative in Increasing Early Childhood Creativity. This research aims to explain how innovative learning models, namely constructivist and cooperative learning, can increase the creativity of early childhood. The method used in this research is qualitative research. This research was carried out by collecting references through books and research journal articles from various parties which have been published in information media and the latest news on internet websites. The reference materials used have been adapted to the discussion topic which is still the same as the discussion title of this article. And the results of this research are by playing constructive games and by forming groups. The impact of the innovative learning model, namely constructivist and cooperative learning, is that it is able to increase the creativity of early childhood. Apart from that, children can develop intellectually.